RELAÇÃO ENTRE ESTILO DE LIDERANÇA E COMPROMETIMENTO ORGANIZACIONAL AFETIVO - Nogueira, Maria de Lourdes de Oliveira (2014)
The organization needs a human capital actually willing to contribute their strategies and goals. Various studies have demonstrated that peoples commitment influences the results. What else is related to performance is affective commitment. The leaders, through their styles may also contribute to generate a performance and better results for organizations. The objective of this research was to analyze the relationship between leadership styles and affective organizational commitment. Using quantitative instrument method for data collection was built up a self-administered questionnaire consists of three scales measuring the variables of the research. The data, all the numerical data, formed an electronic database that was analyzed using descriptive and multivariate statistics of the Pearson correlation of SPSS software, version 19.0 test. The survey was conducted with 92 employees of a private company in the city of São Paulo, using the scale of Smith (2008) to measure affective organizational commitment of workers and scale for assessing the management style of Melo (2004) to identify the profile of leaders of these workers in view of the same, but with variations depending on the sample size, revealed by the value of the Students t- test in bootstrap. Task, relationship and situational with affective organizational commitment correlations between the three leadership styles were analyzed.The analyzes revealed weak correlations between leadership styles and affective organizational commitment, being significant (less than 5 per cent error) the correlations of the commitment to the task with style and situational style, though with variations depending on the sample size. These results contribute to the improvement of people management processes and are useful in the areas of Human Resources in general, to promote improvements in the development of leadership and commitment of the people through the organizations policies.